Level of awareness of selected university students on stress urinary incontinence in women - Zyznawska, Joanna; Buksa, Marcelina; Załęcka, Monika; Królikowska, Aleksandra; Lipiński, Kacper (Health Promotion & Physical Activity, 2019)
Introduction: Stress urinary incontinence is one of the most common chronic pathologies of women. It has a significant impact on all spheres of life, at the same time degrading its quality. It is not only a huge medical problem but also a social and psychological problem. The aim of the study was to examine the level of awareness and knowledge of medical and non-medical students about stress urinary incontinence. Material and methods: The study was conducted electronically using a proprietary questionnaire consisting of 24 questions. The study was attended by 107 women, including 71 female medical students and 36 non-medical students, aged 20 to 26 years. Results analysis was evaluated using the Statistica 13 program. In all tests carried out (Pearson's Chi-2 test), a significance level of 0.05 (p = 0.05) was adopted. Results: The students have an average level of knowledge about stress urinary incontinence. There were statistically significant differences in the level of knowledge between students of different faculties. A group of female medical students had more complete knowledge. Conclusions: There is a need for continuous education of women of all ages in the field of prophylaxis, risk factors and treatment of stress urinary incontinence.